2018
DOI: 10.1111/1462-2920.14311
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial dynamics in microbial community composition within a temperate stream network

Abstract: The water column of streams hosts a unique microbial community that is distinct from the microbial communities of the stream benthos and surrounding soil. This community is shaped by complex interacting forces, including microbial dispersal from surrounding environments and in-stream selection. However, how the processes structuring stream communities change over space and time remains poorly understood. In this study, we characterize spatial and temporal trends in microbial community composition throughout a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
6
33
0
Order By: Relevance
“…The transport of microbes from soils to small streams was previously shown using DNA sequencing techniques and this transfer has been hypothesized to alter downstream microbial communities (Crump et al 2012;Ruiz-González et al 2015;Savio et al 2015). Bacterial transfer to streams was also shown to vary throughout the year and in response to changes in temperature and precipitation (Hassell et al 2018;Hermans et al 2019;Teachey et al 2019). However, DNA sequencing data do not provide quantitative information and, to this day, little is known about the dynamics and seasonality of bacterial abundances in small headwater streams (Richardson 2019).…”
Section: Introductionmentioning
confidence: 93%
“…The transport of microbes from soils to small streams was previously shown using DNA sequencing techniques and this transfer has been hypothesized to alter downstream microbial communities (Crump et al 2012;Ruiz-González et al 2015;Savio et al 2015). Bacterial transfer to streams was also shown to vary throughout the year and in response to changes in temperature and precipitation (Hassell et al 2018;Hermans et al 2019;Teachey et al 2019). However, DNA sequencing data do not provide quantitative information and, to this day, little is known about the dynamics and seasonality of bacterial abundances in small headwater streams (Richardson 2019).…”
Section: Introductionmentioning
confidence: 93%
“…There are a few studies that specifically had the aim to simultaneously investigate community assembly processes over multiple spatial scales (Ramette and Tiedje, ; Martiny et al ., ; Shi et al ., ; Comte et al ., ; O'Brien et al ., ; Hassell et al ., ), that could be used to test our conceptual model. For instance, Martiny et al .…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 99%
“…There are a few studies that specifically had the aim to simultaneously investigate community assembly processes over multiple spatial scales (Ramette and Tiedje, 2007;Martiny et al, 2011;Shi et al, 2015;Comte et al, 2016;O'Brien et al, 2016;Hassell et al, 2018), that could be used to test our conceptual model. For instance, Martiny et al (2011) compared the effect of environmental and spatial variables on ammonia-oxidizing bacterial communities in marshes at three spatial scales (within marshes, among marshes and among continents) and found the strongest spatial effects at the within-marsh scale, i.e., at spatial scales ranging between a few centimetres up to 1 km.…”
Section: Spatial Scalementioning
confidence: 99%
“…Temporal trends in community profiles have been described in many riverine systems (3,(5)(6)(7)(12)(13)(14)(15)(16)(17)(18). In several of these studies, the same taxa were found over time, varying in abundance based on shifts in physiochemical factors or following landscape-level disturbances (5,10,13,(17)(18)(19)(20). This reoccurrence of taxa has led several groups to suggest the presence of a core community that is of particular importance in shaping riverine community dynamics (2,9,10,13,(21)(22)(23).…”
mentioning
confidence: 99%
“…appears to be soil and soil waters (1,2,8,12), with pelagic stream community assembly resulting from the enrichment of bacteria present in these environments at low abundance. From the headwaters, the bacterioplankton community continues to develop as it travels through the stream network (10,11,13).…”
mentioning
confidence: 99%